Polymorphism in the second intron of the FGFR2 gene rs1219648 associated with the early-onset breast cancer in Turkish population - Taskin, Irmak Icen; Tekin, Mehmet A.; Pektanc, Gulsum; Munzuroglu, Omer; Kandemir, Sevgi Irtegun (E-Century Publishing Corp, 2017)
The incidence of early-onset breast cancer has been increased up to 25% in the developing countries. Several studies reported that breast cancer cases in younger women have different biological characteristics than others. These patients should be studied separately. Lack of the necessary information about the younger patients prevents significant improvements about diagnosis and treatment strategies targeting these patients. Polymor-phisms within intron 2 of the FGFR2 gene have been associated with postmenopausal breast cancer patients in many populations. However, there exists no research on the impact of rs1219648 on early-onset breast cancer in Turkish population. In this study, the association of rs1219648 with early-onset breast cancer in Turkish women has been investigated. A total of 171 subjects, including 75 female breast cancer patients who were less than or equal to 40 years of age and 96 age-matched healthy controls were recruited. Our results indicate that G allele of the rs1219648 is statistically correlated with early-onset breast cancer (OR 2.0098, 95% CI 1.3016-3.1032, P=0.002). When rs1219648 was examined as a categorical variable where the reference category related to the wild-type genotype (AA), the calculated OR was [2.112 (95% CI 0.9904-4.5058), P= 0.053], and [5.2308 (95% CI 1.939114.1102), P=0.001], for genotypes AG and GG, respectively. We present the first report on FGFR2 rs1219648 polymorphism in early-onset breast cancer in Turkish women. Our results propose that rs1219648 polymorphism individually confers susceptibility for development of early-onset breast cancer in the Turkish populations.
Keywords: rs1219648; FGFR2 gene; early-onset breast cancer; cancer susceptibility; Turkish women